Visitors' Perceptive Agent (VPA) on museum indoor environment - Sulaiman, Raha; Kamaruzzaman, Syahrul Nizam (2014)
This research is made to investigate what effect the museums' indoor environmental quality (IEQ) has had upon visitors' satisfaction and their temporal discomfort symptoms (TBS) perceptively. Eight historical and air-conditioned museums mainly located in Peninsular Malaysia were selected. A total of valid 546 respondents completed the questionnaire based on convenience sampling. Derived from modified existing IEQ models, this study analysed the proposed factors and their relationships in a structural equation model (SEM) to suit with museum indoor environment. The hypothesised relationships are subsequently tested by means of the partial least squares (PLS) path modelling approach. SEM path model represents the hypotheses acceptance for the direct effect of all environmental factors on visitors' satisfaction except for the deletion of thermal environment. Only two TBS supported the direct effect hypotheses on visitors' satisfaction; emotion and eyes. Whereas the environmental factors that affect visitors' on few discomfort symptoms are exhibition environment on eye and IAQ on emotion, NSB and throat.